SETTLEMENT OF INHERITANCE IN THE FORM OF LOAN CAUSED BY DEFAULT BY ONE OF THE HEIRS (A Case Study on the District Court’s Verdict No. 46/Pdt.G/2015/PN.Mdn) - NURFIKA AFNI (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1. Prof. H.M. Hasballah, SH, MHum2. Dr. Utary Maharany Barus, SH, MHum3. Dr. Yefrizawati, SH, MHumInheritance law states that death causes inheritance. In consequence, allof a deceased person’s property will automatically goes down to the heirs.Usually, inheritance is distributed in cash; but in this case, the inheritance is inthe form of loan as it is stipulated in the Verdict No. 46/Pdt.G/2015/PN.Mdn.The thesis used juridical normative and descriptive analytic method.Secondary data were gathered by conducting library research and analyzedqualitatively, while the conclusion was drawn deductively.The result of the research shows that debt and credit among heirs towardinheritance collected physically or calculated before it can be distributed to heirs.Priority is given to zul furudl heir since his right is clearly described in the Koran.Some methods in settling loan inheritance due to one of the heirs’ default areSulhu, Ibra, and Hajr. In this case, sulhu is the most appropriate method insettling the dispute by negotiation to avoid prolonged dispute and to make thefamily tries between defendant and the plaintiff harmonious. The Panel of Judgesstate that the Deferndant is required to pay off his debts to the Plaintiff based onpromissory note ad since the Defendant does not have evidence which will stateon reverse.Keywords: Inheritance, Debt and Credit, Default, Heirs